2022
DOI: 10.1002/ejp.1914
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine in chronic pain: A Delphi survey

Abstract: Background: There is no recommendation in Europe for the use of ketamine in patients with chronic pain. The heterogeneity of practice highlights the need to seek the advice of experts in order to establish a national consensus. This Delphi survey aimed to reach a national consensus on the use of ketamine in chronic pain in Pain clinics.Methods: A collaborative four-round internet-based questionnaire was used. It was created after literature search on ketamine administration in chronic pain and included about 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…The link between depression alleviation (especially for depression with suicidal ideations) 6 , 28 and pain relief 5 with ketamine treatment is complex. 24 , 29 Comorbid pain and depression are frequent, with a bidirectional interaction, 26 , 30 but a recent activation likelihood estimation meta-analysis 31 stresses that the direction of comorbidity (ie, pain with depression vs depression with pain) is rarely addressed and may concern different cerebral areas and neurobiology mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The link between depression alleviation (especially for depression with suicidal ideations) 6 , 28 and pain relief 5 with ketamine treatment is complex. 24 , 29 Comorbid pain and depression are frequent, with a bidirectional interaction, 26 , 30 but a recent activation likelihood estimation meta-analysis 31 stresses that the direction of comorbidity (ie, pain with depression vs depression with pain) is rarely addressed and may concern different cerebral areas and neurobiology mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Drug management of chronic pain with antidepressants, antiepileptics, and opioids remains inconclusive, as 60% of patients show little improvement, experience adverse effects, and often require other treatment options . Ketamine, a nonselective N -methyl- d -aspartate receptor (NMDAR) antagonist with anesthetic properties, can relieve chronic pain . A recent clinical study in patients with refractory chronic pain identified distinct pain relief trajectories with variables that are associated with the response to a single dose of ketamine according to pain characteristics, level of anxiety, depression, or quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 However, in recent years, poorly regulated 'ketamine clinics' for chronic pain (and depression) have sprouted worldwide, 11,15 with frequent administration reported in the US, the Netherlands, France, South Korea, and the UK. 8,[37][38][39] As such, ketamine for chronic pain has bypassed the traditional, rigorous drug development sequence involving initial animal testing, then human experimental studies and clinical trials assessing efficacy and safety, followed by strict surveillance. 11 The first ketamine clinic that opened in the UK was in Bristol, charging £6000 for a course of low-dose infusions with psychotherapy for depression.…”
Section: Introductionmentioning
confidence: 99%
“…11,14,37 Surveys of pain clinics in France, South Korea, and the Netherlands have demonstrated this variability between practices, including the dose, duration, and monitoring facilities, but they report that serious adverse events are rare. [37][38][39] Therefore, although these widely varied protocols suggest a lack of evidencebased prescribing, they appear to be well-tolerated in general, particularly when accounting for the likely significant disease burden of eligible patients prior to SDKI administration. 4 In addition, the monitoring and documentation of side effects in both the research and clinical setting may be aided by the recently developed Ketamine Side Effect Tool (KSET).…”
Section: Introductionmentioning
confidence: 99%